Advances in polymer science = Fortschritte der Hochpolymeren-Forschung. Volume 9 - Cantow, H. J. (Springer-Verlag, 1972)
Zustände and Reaktionen des Caranions bei der anionischen Polymerisation des Styrols / Böhm, L.L., Chmeliř, M., Löhr, G. Scmitt, B.J., Schulz, G.V. ; Polymerisationsanregung durch Elektrolyse / Breitenbach, J.W., Olaj, O.F., Sommer, F. ; Treatment of the folding and unfolding of protein molecules in solution according to a lattice model / Hermans, jr, J., Lohr, D, Ferro, D ; Inelastic laser light scattering from bioilogical and synthetic polymers / Peticolas, W.L.
Keywords: polymery; polymerizace; polystyren; instrumentální analýza; biopolymery; bílkoviny; polymers; polymerization; polystyrene; instrumental analysis; biopolymers; proteins; sborníky; miscellanea